High-performance, low-voltage organic field-effect transistors using thieno[3, 2-b]thiophene and benzothiadiazole co-polymers. Issue 21 (16th May 2022) - Amna, Bibi; Isci, Recep; Siddiqi, Humaira M.; Majewski, Leszek A.; Faraji, Sheida; Ozturk, Turan
Abstract : A series of new linear conjugated polymers incorporating different substituted thieno[3, 2- b ]thiophenes as donor, acetylene as π-bridge and benzothiadiazole as acceptor units were synthesized via Pd-catalyzed Sonogashira cross-coupling polymerization. Abstract : A series of new linear conjugated co-polymers, incorporating different substituted thieno[3, 2- b ]thiophenes (TTs) as the donor, acetylene as the π-bridge and benzothiadiazole (BT) as the acceptor units, were synthesized via palladium-catalyzed Sonogashira cross-coupling polymerization. The optical, electrochemical, and thermal properties of these conjugated polymers were evaluated via UV-vis, fluorescence, cyclic voltammetry, and thermogravimetric analysis. These readily soluble TT–BT co-polymers were employed as the semiconducting channel materials in bottom-gate, top-contact (BGTC) organic field-effect transistors (OFETs). The OFET devices showed p-channel field-effect behavior and successfully operated below −3 V in high yield. The polymeric materials comprising TTs with aliphatic side chains exhibited a better OFET performance compared with those with aromatic side chains. The OFETs using TT–BT with thienothiophene bearing a nonyl (C9 H19 ) side chain showed the highest hole average carrier mobility in the saturation regime, μ sat = 0.1 cm −2 V −1 s −1, on/off current ratio, I ON / I OFF = 3.5 × 10 3, and the smallest subthreshold swing, SS < 200 mV dec −1 . The observed differentiation in device characteristics can be beneficial in applications where selectivity is as essential as the field-effect behavior.